Schnitzler’s syndrome with IgA-IgG paraproteinemia and acquired cutis laxa. - Garofalo, L.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2011)
Case report. A 78-year-old woman presented from 6 years progressive weakness, arthralgias of the scapular and pelvic girdles and febricula. The patient also reported asymptomatic short-lasting erythematous manifestations and from about two years rapid aging of the skin with formation of deep wrinkles. On physical examination urticaria and acquired cutis laxa were diagnosed, the latter being particularly evident in the face (Fig. 1, before falling ill, provided by the patient and Fig. 2 after 2 years) and limbs (Fig. 3). Liver, spleen and lymph nodes were not enlarged. The nonspecific inflammatory indexes were increased with monoclonal gammopathy IgAk and IgGk. The skin biopsy confirmed the diagnosis of urticaria. An ultrasound scan showed lesions of the rotator cuff in her right shoulder. The final diagnosis was Schnitzler’s syndrome with IgA and IgG paraproteinemia and acquired cutis laxa.